Biomacromolecular-based ionic-covalent hydrogels for cell encapsulation: The atelocollagen − Oxidized polysaccharides couples. (1st August 2017) - Luca, Andreea; Maier, Vasilica; Maier, Stelian S.; Butnaru, Maria; Danu, Maricel; Ibanescu, Constanta; Pinteala, Mariana; Popa, Marcel
Highlights: Atelocollagen, hyaluronate and oxidized polysaccharides generate stable hydrogels. Cells can be encapsulated during the thermal activated gelation of the mixture. Optimal formulation corresponds to an atelocollagen:polysaccharides ratio of 3:1. Oxidized gellan provides better and more reproducible cell embedding characteristics. Encapsulated cells can be released in cell-protective conditions, by thermal shock. Abstract: Mixed crosslinked networks of ionic-covalent entanglement type were prepared starting from ternary mixtures of atelocollagen (aK; as fibrillary matrix generator), sodium hyaluronate (NaHyal; a microfibrillation assistant), and oxidized polysaccharides (OxPolys; as both cross-linkers and matrix fillers), and were tested as hydrogels for eukaryotic cell encapsulation. Either oxidized gellan (GellOx) or pullulan (PullOx) were used. An original procedure and optimal hydrogel recipes were developed to encapsulate fibroblasts and adipose-derived stem cells, while preserving their viability and proliferative ability during ex vivo temporarily storage. Physical-chemical, rheological, and biocompatibility properties of the prepared hydrogels were compared against the classic alginate hydrogel used for cell encapsulation. A larger range of material characteristics (from lax to stiff) and better laboratory maneuverability were demonstrated, which permit to design appropriate compositions for particular cell types. All hydrogels undergo fast liquefaction at temperatures between 42 and 50 °C, permitting the cell release after a short innocuous thermal shock.